2003
DOI: 10.1136/jcp.56.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue, pelvic, and urinary bladder leiomyosarcoma as second neoplasm following hereditary retinoblastoma

Abstract: This report describes two patients who developed leiomyosarcomas, one involving the subcutaneous tissue of the thigh and the pelvic soft tissues and the other the urinary bladder, following hereditary retinoblastoma 36 and 38 years earlier, respectively. There is an increased risk of the development of sarcoma, most commonly osteosarcoma, as a second malignancy following hereditary retinoblastoma. Leiomyosarcoma developing as a second malignancy has rarely been reported and most have occurred in the field of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…One case describes LMS of the retroperitoneum [15], while Fletcher et al describe a hereditary retinoblastoma patient with adenocarcinoma of the uterus [16]. Our robust long-term follow-up allows for more patients entering the age when ULMS are commonly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…One case describes LMS of the retroperitoneum [15], while Fletcher et al describe a hereditary retinoblastoma patient with adenocarcinoma of the uterus [16]. Our robust long-term follow-up allows for more patients entering the age when ULMS are commonly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports describe three patients who developed leiomyosarcomas, one involving the subcutaneous tissue of the thigh and the pelvic soft tissues and the other the urinary bladder, following hereditary retinoblastoma 36, 38 and 49 years earlier, respectively [51,52]. We also have reported a case of primary bladder LMS in a 45-year-old woman with a history of hereditary Rb.…”
Section: Tumor Suppressor and Oncogenic Pathway In Ut-lmsmentioning
confidence: 79%
“…The RB gene is a tumor suppressor gene encoding a nuclear phosphoprotein that functions as a regulator of cell cycle progression. Patients with hereditary retinoblastomas are probably at increased risk of developing leiomyosarcoma and other soft-tissue sarcomas [10]. A review of the literature revealed also an increased prevalence for leiomyosarcoma of the urinary bladder in cyclophosphamide-exposed patients treated for other malignant conditions [3,[11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%